(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The juvenile case was one of the most controversial issues in the country, with citizens demanding that the juvenile rapist be tried as an adult because it was such a horrible act. Juvenile delinquency has been identified as a major issue in India and around the world. There is no denying that today’s delinquent boy, if not properly cared for, will become a criminal tomorrow. Children’s delinquency should be controlled until it becomes a major threat to society. According to statistics presented by different agencies from time to time, the number of juvenile crime cases is on the rise. There is a need for a comprehensive investigation into the numerous facts and causes that contribute to delinquencies, disorderly behaviour, public indecency, and child-law conflict, as well as the problem’s solution, which includes proper care and rehabilitation of the delinquent child.